KORELASI PENGGUNAAN INTERNET SEBAGAI SUMBER BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP KETERLIBATAN MAHASISWA DALAM PROSES PEMBELAJARAN DI UIN ANTASARI BANJARMASIN - Makherus Sholeh (JP : JURNAL PENDIDIKAN, 2019)
Abstract: The purpose of this research is to measure the correlation of internet usage as a source of learning and learning independence towards the involvement of new students in the learning process at UIN Antasari Banjarmasin. The research method used is a mixed method using an explanatory sequential design. The study population was all 2017 new students of UIN Antasari Banjarmasin in 2017 with a sample of 317. Results 1) The use of the internet as a learning resource is low, 2) Independence of students in the low category, 3) student involvement in the learning process in the low category, 4) The effect of internet usage as a learning resource on the involvement of UIN Antasari Banjarmasin new students in the learning process is in a fairly strong category, 5) The effect of learning independence on the involvement of new UIN Antasari Banjarmasin students in the learning process is in the strong category, 6) The effect of internet usage as a learning resource and learning independence on the involvement of new UIN Antasari Banjarmasin students in the learning process is 62.85% rounded off to be 62.9%. 7) Other factors that influence the involvement of new UIN Antasari Banjarmasin students in the learning process are the profile of the lecturer, the demands of parents and academic competition between students.Keywords: Use of the Internet as a Learning Source, Independently Learn, Learning Process